Gambaran Pengalaman Flow Pada Mahasiswa Yang Bekerja Part-time - Zidna Rohmatika; Muhammad Arif Budiman Sucipto (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
Part-time working students face challenges in balancing academic and work demands, which can affect their learning engagement. This study entitled